Materi Dakwah dalam Website Dakwatuna.com - Claudira Agustika (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2019)
Da'wah is a communication practice. Da'wah is one of the communication activities because in da'wah there is a process of transmitting information (messages) from the communicator (da'i, interpreter) to the communicant (mad'u) through various media such as newspapers, radio, television, and the internet. Da'wah activities will be able to run effectively and efficiently when using strategic and appropriate ways of conveying the teachings of Allah SWT. This study aims to find out the da'wah materials found on the website dakwatuna.com. This study uses a qualitative method with a content analysis approach. The focus of this research is the texts contained on the website dakwatuna.com which were published from April to July 2016. The results of the research that the website of dakwatuna.com is part of the propaganda media that presents valuable information, knowledge and articles for people and civilization. The response of internet users is very enthusiastic and extraordinary about the material presented by the website dakwatuna.com. The material presentation on the dakwatuna.com website includes aspects of da'wah material namely aqeedah, sharia and morality. Aqeedah material found in the material do not sacrifice your religion, the prohibition on dreaming of hoping for death, do we remember the traffic jam in the Mahsyar field. In sharia material found in the material of marriage, what is the theme of our Ramadhan, four practices of heaven in one day, zakat is empowering and loving because of Allah. Whereas in the material of morality that is practicing sincerity, three saviors and three destroyers, the dream house and when the mother fell asleep.